From Henshin Belt to Wearable Tech: A Study on Pop Culture Accessory Design in The Creative Industry - Atamtajani, Asep Sufyan Muhakik (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2025)
This research examines the transformation of accessories in popular culture, particularly the concept of the Henshin Belt from the Kamen Rider series and its influence on the development of wearable technology in the creative industry. The aim of this study is to analyze how the design of the Henshin Belt has evolved and influenced trends in technology-based accessories, such as smartwatches, augmented reality (AR) devices, and interactive fashion. The research uses a qualitative method with a semiotic analysis approach, employing data collection techniques through literature review, visual analysis, and comparative study. The analysis technique used is visual semiotic analysis to examine the relationship between popular culture aesthetics and technological development in product design. The results of this study show that the Henshin Belt has undergone significant evolution, from a simple mechanical device to an interactive digital tool that enhances user experience. The concepts of interactivity and identity embedded in the Henshin Belt laid the foundation for the increasing popularity of wearable tech in the creative industry. This study contributes to understanding how popular culture artifacts can inspire technological innovation and influence product design strategies. Future research could explore user perceptions of these accessories and their impact on the global wearable tech market.